Screening and characterisation of BCR::ABL1 kinase domain mutations in chronic myeloid leukaemia participants at Tygerberg Hospital, South Africa - Shareefa, Isaacs (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMed)--Stellenbosch University, 2023.